Vplivi spleta na slovensko ulično poezijo - Kusterle, Jernej (Slavistična revija, 2015)
With the internet, numerous linguistic innovations were introduced into Slovene street poetry, i.e., they were adopted and integrated into lyrics by Slovene street poets. On one hand, these changes were useful, as the vocabulary became more current and closer to the everyday usage, but on the other hand this new media opened the question whether a stylistically marked word that appears on the internet and is transferred into general use by a young poet is already slangism or not. Slovene street poetry was affected by the internet in other ways, i.e., in terms of its transmission models, communicative options, advertising, marketing, and self-promotion.
Keywords: e-jezik; e-language; glasba; internet; music; phonetism; rap; rapping; Slovene; Slovenian language; slovenščina; street poetry; ulična poezija